PERTUMBUHAN DAN PRODUKSI JAGUNG PULUT (Zea mays ceratina) DENGAN PEMUPUKAN ANORGANIK DAN PUPUK KANDANG DIPERKAYA N-ORGANIK DAN P-ALAM - Ratna Dwi Kartikasari; Dwi Retno Lukiwati; Didik Wisnu Widjajanto (Percetakan Umi Toaha Makassar, 2022)
The growth and yield of waxy corn are determined by organic and inorganic fertilizers. The addition of organic-N (N-Leucaena leucocephala) and nature-P (P-rock phosphate) can be used as a substitute for inorganic fertilizers (urea and TSP). The present study investigated the effects of N-leucaena leucocephala and P-rock phosphate enriched manure (manure plus) on the growth and yield of waxy corn. The experiment was conducted in a randomized complete block design with seven treatments and four replicates: T0 (urea + TSP), T1 (urea+TSP + cattle manure), T2 (urea+TSP + goat manure), T3 (urea+TSP + poultry manure), T4 (N-L. leucocephala+ P-rock phosphate + goat manure), T6 (N-L. leucocephala+ rock phosphate + poultryobserved were plant height, chlorophyll content, cob weight with cornhusk and without cornhusk, and cob length with cornhusk and without cornhusk. The data was analyzed using analysis of variance, followed by Duncan's multiple range tests.The results showed that manure plus had a significant effect (P<0.05) on cob weight with cornhusk and without cornhusk and cob length without cornhusk. The parameters of plant height, leaf chlorophyll content, and cob length with cornhusk were similar in all treatments. Based on the research results, it may be concluded that the addition of Leucaena leucocephala and rock phosphate to manure can improve the quality of the organic fertilizer and can replace inorganic fertilizer.